Characterization and validation of the nonlinear viscoelastic-viscoplastic with hardening-relaxation constitutive relationship for asphalt mixtures. (20th August 2019) - Darabi, Masoud K.; Huang, Chien-Wei; Bazzaz, Mohammad; Masad, Eyad A.; Little, Dallas N.
Highlights: A coupled viscoelastic, viscoplastic and hardening-relaxation model is proposed. A systematic analysis procedure is developed to extract the model parameters. The model can simulate the asphalt material behavior under various loading paths. The analysis procedure identifies the model parameters using simple tests. Abstract: This paper presents a systematic and straightforward analysis procedure to extract the material parameters associated with a coupled nonlinear viscoelastic (VE), viscoplastic (VP), and hardening-relaxation (HR) constitutive model for asphalt mixtures. The recoverable and irrecoverable strain are represented by Schapery nonlinear VE model and Perzyna-type VP theory, respectively. A HR model is proposed to consider the relaxation of hardening. Dynamic moduli and repeated creep-recovery tests are used to calibrate the coupled VE-VP-HR model. The model is then validated against independent experimental data. Results show that the VE-VP-HR model has the ability to capture the response of asphalt mixtures subjected to various loading paths.